An analysis of TOEFL® Primary™ repeaters: How much score change occurs?. (October 2020) - Cho, Yeonsuk; Blood, Ian A.
In this study, we examined how much change in TOEFL ® Primary ™ listening and reading scores can be expected in relation to the time interval between test administrations. The test records of 5213 young learners of English (aged 8–13 years) in Japan and Turkey who repeated the tests were analyzed to examine test scores as a function of time interval. The effect of time on test scores was analyzed with a multilevel modeling approach, allowing both initial scores and rate of change among individual test takers to vary. In addition, we examined the effects of test-taker age and test-level difficulty on test scores. Separate analyses were conducted by country for ease of interpretation, as Japan and Turkey differ with respect to the number of hours of instruction that students receive and the English-learning goals in their respective curricula. Results showed a positive rate of change, indicating that test scores increase gradually over time. However, the rate of change differed between the two countries. Furthermore, repeaters' test scores increased with their age and with the length of time between test administrations. Findings provide empirical evidence for schools to refer to when determining the timing of re-administration of the TOEFL Primary tests to their students.